Volume 5: Education and Globalization 2014
DOI: 10.1115/imece2014-39698
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Similarity Flooding Algorithm to Solve Engineering Problems Using Diagnostic Skills Training Technique

Abstract: This article focuses on the development and field testing of instructional design concepts and educational software to teach diagnostic skills necessary to identify and solve problems in complex technical systems. Using concept mapping software along with expert-system programs, the overall software package enables technical workers and students in technology and engineering fields to benefit from personalized, iterative interactions that permit them to design visual maps of a diagnostic strategy and to allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Our method of comparing concept maps is based on combining the weighting mechanism, SFA, and semantic similarity of two strings. The detail introduction of the method is included in the paper by Shahhosseini et al 29 .…”
Section: Assessment Methodsmentioning
confidence: 99%
“…Our method of comparing concept maps is based on combining the weighting mechanism, SFA, and semantic similarity of two strings. The detail introduction of the method is included in the paper by Shahhosseini et al 29 .…”
Section: Assessment Methodsmentioning
confidence: 99%
“…Prior work by Shahhosseini served as a foundation for machine-based diagram evaluation [43][44][45][46]. Software was developed to compare two node-and-link diagrams and produce an overall similarity rating.…”
Section: Systems Thinking In Context Of Technological and Engineering Literacymentioning
confidence: 99%
“…Our method of comparing concept maps is based on combining the weighting mechanism, SFA, and semantic similarity of two strings. The detail introduction of the method is included in the paper by Shahhosseini et al 14 and shown in Figure 2. In Figure 2, we adopt SFA program (Open source Java code developed by Melnik et al) to match the nodes based on their relationships.…”
Section: Figure 1: the Process Of Comparison For Process Mapsmentioning
confidence: 99%